Assessing risk management maturity for construction projects in Jabatan Kerja Raya (JKR) / Saiful Jumali - Jumali, Saiful (2014)
Under the Ninth Malaysia Plan (9MP), Jabatan Kerja Raya (JKR) was burdened by too many projects. Therefore, financial and time losses sometimes occurred during the process of building procurement until project implementation when managing risks not properly. The aim of this study was to assess the maturity of risk management for construction projects in JKR. In order to achieve this aim, three objectives have been outlined in this study; to establish the relationship between attributes, to identify the high influence indices of risk management attributes for construction projects in JKR and to identify the current overall risk management maturity for construction projects in JKR. In this study, four attributes were chosen for JKR risk management maturity model. The four attributes namely culture/ awareness, experiences, processes and practices. Therefore, in this study had used four levels of maturity namely level 1: Initial, level 2: Established, level 3: Managed and level 4: Optimized. This study was conducted using a questionnaire survey among professional in all JKR branches which cover business sector, management sector, expert sector and JKR state. A total of 133 out of 580 completed questionnaires were returned. This research found a strong and positive relationship between processes attribute and experiences attribute [r=0.781,N=133, p=0.0005]. The high influence indices of risk management attributes for construction projects in JKR was the acceptance of risk management in JKR. The empirical research findings showed that the overall risk management maturity levels for construction projects in the JKR were 2.52. The four (4) attributes to assess risk management maturity for construction projects in JKR namely culture/ awareness, experiences, processes and practices were achieved between level 2 and level 3 or between “managed" and “optimized” based on the JKR Risk Management Maturity Model proposed in this research.